A powered bone marrow biopsy system versus manual methods: a systematic review and meta-analysis of randomised trials. Issue 9 (1st June 2013) - Voigt, Jeffrey; Mosier, Michael
Abstract : A significant number of bone marrow biopsies are performed annually. Outcomes of patient pain and sample size of biopsy are important issues as perception of patient pain is underestimated by clinicians and sample size assists in accurate diagnosis. Manual extraction of marrow biopsy is the main method used. Recently a powered system has been introduced. The objectives of this systematic review and meta-analysis were to determine if the powered system reduces patient pain and improves sample capture. A PubMed and Cochrane search for randomised controlled trials was undertaken comparing the powered system with manual methods. Risk of bias assessment and meta-analysis of outcomes using appropriate statistical methods were performed. Five randomised controlled trials were identified. Patient pain (measured via visual analogue scale (VAS)—100 point scale) was significantly reduced using the powered system: mean difference=−6.57; 95% CI −12.93 to −0.22; p=0.04. The relative reduction in pain was 17%–25% with the powered system. Sample biopsy size (length in mm) was also significantly increased with the powered system: mean difference=3.65 mm; 95%; CI 1.61 mm to 5.68 mm; p=0.0005. The relative increase in sample size was 33% with the powered system. Operator ease of use (as measured via VAS) and adverse events were similar. Despite limited operator experience, patients experienced less pain and sample sizes were increased without an increase in adverse events with the powered system. The powered system may offer an option in obtaining samples from patients whose pain is compromised by disease and may reduce redos.